Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
To integrate (x^2+1)/(x^2-1), use partial fractions and substitution.
First, factor the denominator: x^2-1 = (x+1)(x-1)
Then, write the fraction as a sum of partial fractions: (x^2+1)/(x^2-1) = A/(x+1) + B/(x-1)
To find A and B, multiply both sides by the common denominator (x+1)(x-1) and simplify: x^2+1 = A(x-1) + B(x+1)
Substitute x=1 to eliminate A: 2 = 2B, so B=1
Substitute x=-1 to eliminate B: 2 = -2A, so A=-1
Therefore, (x^2+1)/(x^2-1) = -1/(x+1) + 1/(x-1)
Integrate each term separately using substitution:
∫-1/(x+1) dx = -ln|x+1| + C
∫1/(x-1) dx = ln|x-1| + C
Therefore, the final answer is:
∫(x^2+1)/(x^2-1) dx = -ln|x+1| + ln|x-1| + C
Simplify using logarithmic rules:
∫(x^2+1)/(x^2-1) dx = ln|(x-1)/(x+1)| + C
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.